Cardiac alterations following experimental hip fracture - inflammaging as independent risk factor - Lackner, Ina; Weber, Birte; Preßmar, Jochen; Odwarka, Anna; Lam, Charles; Haffner-Luntzer, Melanie; Marcucio, Ralph; Miclau, Theodore; Kalbitz, Miriam (Frontiers in Immunology, 2022)
Background: Cardiac injuries following trauma are associated with a worse clinical outcome. So-called trauma-induced secondary cardiac injuries have been recently described after experimental long bone fracture even in absence of direct heart damage. With the progressive aging of our society, the number of elderly trauma victims rises and therefore the incidence of hip fractures increases. Hip fractures were previously shown to be associated with adverse cardiac events in elderly individuals, which have mainly been attributed to pre-conditioned cardiac diseases. The aim of the present study was to investigate the effect of hip fractures on the heart in healthy young and middle-aged mice. Materials and Methods: Young (12-week-old) and middle-aged (52-week-old) female C57BL/6 mice either received an intramedullary stabilized proximal femur fracture or sham treatment. The observation time points included 6 and 24 h. Systemic levels of pro-inflammatory mediators as well as local inflammation and alterations in myocardial structure, metabolism and calcium homeostasis in left ventricular tissue was analyzed following hip fracture by multiplex analysis, RT-qPCR and immunohistochemistry. Results: After hip fracture young and middle-aged mice showed increased systemic IL-6 and KC levels, which were significantly elevated in the middle-aged animals. Furthermore, the middle-aged mice showed enhanced myocardial expression of HMGB1, TLR2/4, TNF, IL1β and NLRP3 as well as considerable alterations in the myocardial expression of glucose- and fatty acid transporters (HFABP, GLUT4), calcium homeostasis proteins (SERCA) and cardiac structure proteins (desmin, troponin I) compared to the young animals following hip fracture. Conclusion: Young and middle-aged mice showed local myocardial alterations, which might predispose for the development of secondary cardiac injury following hip fracture. Age and the age-associated phenomenon of ‘inflammaging’ seemed to be an independent risk factor aggravating and accelerating cardiac alterations following hip fracture.
CRIS-Team Scopus Importer:2022-09-30
Keywords: cardiac inflammation; cardiac structure; hip fracture; inflammaging; proximal femur fracture; secondary cardiac injury

Diaphyseal Femur Fractures in Children and Adolescents-Opportunities and Limitations of the ESIN Technique - Kalbitz, Miriam; Fischer, Andreas; Weber, Birte; Mayer, Benjamin; Lackner, Ina; Preßmar, Jochen (Journal of Clinical Medicine, 2022)
Background: Elastic stable intramedullary nailing (ESIN) is the gold standard for non-overweight children aged 6-12 years. However, the complication rate using elastic stable intramedullary nailing is considerably high. Nevertheless, the question arises of whether the indication for elastic stable intramedullary nailing therapy can be extended and which factors must be taken into account when determining the indication. Methods: A retrospective chart review of patients <18 years admitted with diaphyseal femur fracture at a Level I Trauma Center in Germany between 2005 and 2017 was performed. In total, 118 patients were included. For the classification of femur fractures in children, the AO Pediatric Comprehensive Classification of Long-Bone Fractures (AO-PCCF) was applied. Results: Simple oblique fractures (32-D/5.1) occurred in most of the patients. Patients with simple oblique fractures were significantly younger compared to patients with simple transverse (32-D/4.1) or multifragmentary (32-D/5.2) fracture type according to the AO Pediatric Comprehensive Classification of Long-Bone Fractures. Most patients were treated with elastic stable intramedullary nailing (68 patients, 58%). Although children treated with elastic stable intramedullary nailing were older than those treated conservatively (25%, n = 29, mean age 1.5, median age 1.0), the children in the elastic stable intramedullary nailing group were comparatively young (range 1-12 years, mean age 5.4, median age 5). A total of 32 children below the age of 6 years were treated with elastic stable intramedullary nailing. Complications were more frequent in patients with overhead extension (50%) compared to conservative treatment with a spica cast (17%) or elastic stable intramedullary nailing (15%). Conclusions: Elastic stable intramedullary nailing therapy was associated with a low complication rate and was, therefore, a safe and frequently used treatment strategy in diaphyseal femur fractures with satisfactory results, even though the age groups were expanded in favor of younger patients.
CRIS-Team WoS Importer:2023-01-06
Keywords: diaphyseal femur fracture; child; adolescent; ESIN; AO-PCCF

Immunomodulatory and cardio-protective effects of differentially originated multipotent mesenchymal stroma cells during polymicrobial sepsis in mice - Kanewska, Anna; Lackner, Ina; Friedrich, Anne; Winkelmann, Martina; Rojewski, Markus; Weber, Birte; Preßmar, Jochen; Perl, Mario; Schrezenmeier, Hubert; Kalbitz, Miriam (European Journal of Trauma and Emergency Surgery, 2025)
Purpose: Sepsis is a life-threatening condition with cardiac complications being an independent predictor of poor outcome. Although their mechanisms have been widely investigated, therapeutic options remain limited. One promising therapeutic tool are mesenchymal stromal cells (MSCs). The aim of this study is to investigate the immunomodulatory effects of human MSCs from two different sources (bone marrow/BMMSC and adipose tissue/ASC) and to evaluate their cardioprotective potential. Methods: 60 adult male C57BL/6 mice were divided into sham, sepsis (cecal ligation puncture (CLP)) and two i.v. treatment groups CLP + human BMMSC and CLP + human ASC with 5 animals in each group. The observation periods were 8, 24 and 72 h. Left ventricular tissue was analyzed histologically, by qPCR (C3ar, C5ar1, Il-1b, Il-6, Il-10, Tlr2, Tlr4, Tnfa, and Nlrp3) and western blot. Cardiac damage markers troponin I and heart fatty acid binding protein (HFABP) were detected in serum by ELISA. Results: Troponin I and HFABP were significantly increased in CLP group after 8 h compared to sham. In cardiac tissue the expression of C3ar, C5ar1, Il-1b, Il-6, Il-10, Tlr2, Tlr4, Tnfa and Nlrp3 inflammasome was upregulated up to 24h after CLP compared to sham. After BMMSC treatment, C3ar as well as C5ar, Tlr2 and Il-10 mRNA expression in left ventricle was downregulated compared to CLP, whereas ASC treatment was associated with the downregulation of Il-6 and Nlrp3. Conclusions: CLP-induced polymicrobial sepsis in mice was associated with cardiac damage and increased inflammation in left ventricular tissue. Therapeutic systemic application of human BMMSC and ASC ameliorated damage and inflammation in the heart.
CRIS-Team Scopus Importer:2025-05-02
Keywords: ASC treatment; BMMSC treatment; Cardiac dysfunction; CLP sepsis; Immunotherapy; Septic cardiomyopathy; Tissue regeneration

Radial head and neck fractures in children and adolescents - Kalbitz, Miriam; Lackner, Ina; Perl, Mario; Preßmar, Jochen (Frontiers in Pediatrics, 2023)
Background: Radial head and neck fractures are a rare entity in pediatric patients. Due to specific characteristics of the blood supply and remodeling potential, the correct diagnosis and initiation of appropriate therapy are crucial for the outcome. Therefore, the aim of this retrospective observational study was to present the outcome of a series of pediatric patients with radial head and neck fractures. Methods: In total, 67 pediatric and adolescent patients with a fracture of the proximal radius admitted to a Level I Trauma Center (Germany) between 2005 and 2017 were included in this retrospective observational study. Patients were stratified in accordance with the classification of Judet modified by Metaizeau and with the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF). Results: AO-PCCF fracture type of proximal radius was age-dependent. Epiphyseal axis angle and displacement angle correlated significantly. Fractures treated with a K-wire or embrochage centromedullaire elastique stable (ECMES) presented higher displacement angles. The duration of callus formation was dependent on both the reduction technique and fracture displacement. The range of motion after complete fracture consolidation was dependent on the Metaizeau type and reduction technique but independent of the duration of immobilization and physical therapy. Conclusion and clinical relevance: Both the epiphyseal axis and displacement angle are suitable for measuring the initial fracture displacement in radiographs. Consolidation is dependent on the initial displacement and reduction technique. The mini-open approach leads to a worse reduction result, later callus formation, and a more restricted range of motion in terms of pronation. Furthermore, the range of motion at follow-up is independent of the duration of immobilization and physiotherapy.
CRIS-Team Scopus Importer:2023-02-24
Keywords: AO-PCCF; children; Metaizeau; pediatric fracture; radial head fracture; radial neck fracture